Combining topology and fractal dimension of fracture networks to characterise structural domains in thrusted limestones. (December 2021) - Grodner, Mark W.; Clarke, Stuart M.; Burley, Stuart D.; Leslie, A. Graham; Haslam, Richard
Abstract: Fractures in limestones of the Palaeocene Lockhart Formation in the hanging wall of the Himalayan Main Boundary Thrust north of Islamabad are examined, and the data analysed using a combination of topology and fractal dimension to characterise fracture patterns and relate them to structural domains. Neither technique alone allows the recognition of the structural domains. However, when considered together for all the fractures within an area, fore-thrusts, pop-ups and back-thrusts can be distinguished. The fractures are considered together, as the characteristics of the individual structural domains are characterised by the cumulative effect of all the different fractures, and in these complexly fractured rocks, the concept of fracture sets is problematic. Fore- and back-thrusts have higher fractal dimensions than pop-up structures. The highest fractal dimensions of both types of thrusts occur immediately adjacent to and decrease away from the central pop-up structure. Topologically, fore-thrust domains have fewer fractures and fracture intersections (nodes), with a longer mean fracture trace length; back-thrust domains contain more nodes (hence also more tips, lines, and branches) resulting in higher fracture densities. Pop-up structure domains are characterised by a low fracture intensity. Using the combined analysis of both the topology and fractal dimension, we show that the fracture pattern characteristics are predictable when related to the different structural settings identified within fold and thrust of the Lockhart Formation. Highlights: A new method for characterising fractures in fold-and-thrust belts with complex fracture networks. Reduced time for data collection compared to traditional techniques. Fractal dimensions and topology are combined to characterise fractures in structural domains. Fore-thrusts and back-thrusts have higher fractal dimensions than pop-up structures. Fore-thrusts have fewer longer fractures, back-thrusts have higher densities of connected fractures.